Cytokine Release Syndrome and Associated Acute Toxicities in Pediatric Patients Undergoing Immune Effector Cell Therapy or Hematopoietic Cell Transplantation - Baumeister, Susanne H. C.; Mohan, Gopi S.; Elhaddad, Alaa; Lehmann, Leslie (Frontiers in Oncology, 2022)
Immune effector cells (IEC) are a powerful and increasingly targeted tool, particularly for the control and eradication of malignant diseases. However, the infusion, expansion, and persistence of autologous or allogeneic IEC or engagement of endogenous immune cells can be associated with significant systemic multi-organ toxicities. Here we review the signs and symptoms, grading and pathophysiology of immune-related toxicities arising in the context of pediatric immunotherapies and haploidentical T cell replete Hematopoietic Cell Transplantation (HCT). Principles of management are discussed with particular focus on the intersection of these toxicities with the requirement for pediatric critical care level support.